JAMINAN DALAM PEMBIAYAAN PADA PERBANKAN SYARIAH DI INDONESIA (Analisis Jaminan Pembiayaan Musyārakah dan Muḍārabah) - Muhammad Maulana (Islam Futura, 2014)
The collateral is required to protect Islamic banks from the risk of non-performing financing and other financial lost that might be caused by moral hazard of debtors. There must be a collateral in the form of tabî'iyah contract whether in kafalah or rahn form in order to secure the position of debtors losers action. In fact, Islamic banks have a mandate to manage customer funds with the prudential principle that creditors are able to generate profits that can be shared with creditors. Although the use of rahn and kafalah contract are not well-known in the implementation of musyārakah and muḍārabah contract, using the theory of freedom of contract all the parties can still contract in the main of dictum because the basic principle of contract is permitted in fikih muamalat during the contract or requirement that are made do not contradict with shari'a. The presence of security systems in the theory of musyārakah and muḍārabah doesn’t mean to prohibit using the guarantee, because the use of musyārakah and muḍārabah contract in fikih muamalat is still carried out on the basis of personal trust between the parties. The existence of the guarantee in the contract of muḍārabah and musyārakah are good effort to promote preventive measures using sadd al-zarî'ah pattern so that the funds of creditors which should be protected in according with the concept of maqāsid syarîah should be protected because it is in dharūry level.